Effects of different coverage plants and organic extract on chemical attributes of a loaded arenos clay soil (Research, Society and Development, 2022)
This work aimed to evaluate the effect of the cultivation of different species of cover crops and different fertilizer compositions in relation to the main chemical characteristics of the soil. The state was developed in a commercial area in the period of the first harvest of the years 2020 and 2021, composed of the following treatments: T1 - corn + conventional fertilization, T2 - organic corn, T3 - organomineral corn, T4 - corn + biochar, T5 - mix of cover crops, T6 - corn + Brachiaria, T7 - corn + breviflora, T8 - mix of cover plants + biochar, T9 - millet, T10 - no-tillage + mix of cover plants. Soil samples were collected in the period of November and December of each year and submitted to analysis in relation to the main chemical characteristics of the soil. In general, soil pH values increased from 2020 to 2021, demonstrating that the cover and fertilization managements used increased soil pH. For the values of aluminum and aluminum saturation, effective CTC, sum of bases and saturation by bases there was no significant variation for the treatments. Managements T1, T3 and T6 showed higher calcium contents. There was greater availability of nutrients in the soil as a function of the vegetation cover, mainly for potassium and phosphorus contents.